2021
DOI: 10.1159/000519322
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hyperoxygenation Testing in Fetuses with Hypoplastic Left-Heart Syndrome: Association with Postnatal Atrial Septal Restriction

Abstract: <b><i>Introduction:</i></b> In fetuses with hypoplastic left-heart syndrome (HLHS), maternal hyperoxygenation (MHO) may aid risk stratification. We hypothesized that pulmonary vein (Pvein) velocity time integral (VTI) change with MHO would more reliably identify neonates who undergo emergent atrial septoplasty (EAS) than changes in pulmonary arterial pulsatility index (PA PI). <b><i>Methods:</i></b> Fetuses with HLHS who underwent MHO testing at our institution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Higher Pvein VTI ratios after MHO in the non‐EAS group were observed. The authors concluded that these findings would be more accurate and easier to obtain for a fetal cardiologist endeavoring to distinguish the high‐risk subgroup of HLHS fetuses with RAS than the change in PA proposed by Szwast A. et al 2,21 …”
Section: Mho As a Diagnostic Testmentioning
confidence: 98%
See 1 more Smart Citation
“…Higher Pvein VTI ratios after MHO in the non‐EAS group were observed. The authors concluded that these findings would be more accurate and easier to obtain for a fetal cardiologist endeavoring to distinguish the high‐risk subgroup of HLHS fetuses with RAS than the change in PA proposed by Szwast A. et al 2,21 …”
Section: Mho As a Diagnostic Testmentioning
confidence: 98%
“…39 MHO was proposed as a method to improve the detection of RAS Higher Pvein VTI ratios after MHO in the non-EAS group were observed. The authors concluded that these findings would be more accurate and easier to obtain for a fetal cardiologist endeavoring to distinguish the high-risk subgroup of HLHS fetuses with RAS than the change in PA proposed by Szwast A. et al 2,21 Maternal hyperoxygenation (MHO) as a test seems to be very useful for investigating the hemodynamics of fetuses with CHD and for predicting and stratifying the severity of the malformation. The reaction to oxygen and improvement of cardiovascular parameters in the early third trimester raises the question of long-term oxygen administration to improve outcomes in selected types of CHD (Table 2).…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…The hemodynamic effects of MH have been shown to be useful in prenatal diagnosis and counseling. Acute MH in fetuses with left heart hypoplasia was specifically studied in patients with HLHS and restrictive or intact atrial septum (62,66,71,72). Severe restriction or an intact atrial septum significantly aggravates the overall prognosis in fetuses with hypoplastic left heart syndrome as described above.…”
Section: Acute Hyperoxygenation Testing In Fetuses With Left Heart Hy...mentioning
confidence: 99%
“…Similar findings were reported in a study by Enzensberger et al, also showing that there was no response to acute MH in fetuses with HLHS and RAS (66). Mardy et al (72), however, investigated the effect of acute MH on pulmonary venous return analyzing the pulmonary vein prograde/retrograde VTI ratio (48,(73)(74)(75) with regard to emergent postnatal intervention. Different pulmonary vein flow patterns with increasing restriction of the atrial septum are shown in Figure 5.…”
Section: Acute Hyperoxygenation Testing In Fetuses With Left Heart Hy...mentioning
confidence: 99%
See 1 more Smart Citation